THE ROLE OF CUSTOMS PAYMENTS IN ENSURING ECONOMIC SECURITY (International Congress on Economics, Management and Business Studies, 2026)
In the context of Uzbekistan, ensuring economic security is considered one of the priority directions of state policy. In the conditions of deepening globalization processes and the steady annual growth of foreign trade turnover, protecting the national economy from external risks, maintaining domestic market stability, and strengthening state budget revenues have become increasingly important. In this regard, customs payments play a significant role in ensuring economic security not only as a fiscal instrument but also as an economic regulation mechanism.